Operational Performance of Courier Companies to E-Business Firms: Literature Review - Nurul, Izzah; Liu, Yao; Cheng, Jack Kie; Damhuji, Rifai (Universiti Malaysia Pahang, 2016)
This study aim to reviewing of operational performance in courier service companies as a third party logistics (3PL) to their business partner and customer, which is among them use of technology in business operations. It consists the definitions, process, types, components and theories of operational within joint venture or operations between courier companies their business partner or customers. Firstly we reviewing operational competence before we describe about operational performance based on literature of operational management. Because we found in literature of operation management, that operational performance origin based on operational competence, and operational performance consists of technology utilized for instance e-commerce and e-business systems integration to assist business operations systems with suppliers and customers. We concluded, that logistics suppliers and business partners should have trust because they dependence each other to run business operation, thus from operational performance we can know level of dependence, trust and sale growth of e-business firms with their logistics supplier provided by of courier companies.